FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN PADA KANTOR PELAYANAN PAJAK PRATAMA SEMARANG TENGAH SATU - Intan Yuningtyas Anggraeni; Naili Farida; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2013)
There are four factors on tax compliance, namely: awareness of the taxpayer, the taxpayer opinion about the severity of the burden of income tax, the taxpayer perceptions of the implementation of the income tax penalties, taxpayers and tax evasion inherent in individual taxpayer. The data were obtained through questionnaires with 100 people sample taxpayers tax office in Semarang Tengah Satu. The research method used is a simple regression and multiple regression. The results of this study indicate that there is a positive and significant the adjusted R square value or the coefficient of determination of taxpayer an influence for 56.5% of the income tax revenues. While the remaining 43.5% is the influence of other variables that are not observed. The conclusions of this study based on table F, note that Ho is rejected and Ha accepted, which means that there is a positive and significant.  Advice can be given to taxpayers in order to understand and comply with tax taxation laws such as penalties for taxpayers who violate the rules of taxation and tax payers.